2010
DOI: 10.4103/0971-3026.73537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the styloid process on digital panoramic radiographs

Abstract: Background:The styloid process is an anatomical structure, whose clinical importance is not well understood. Proper clinical and radiographic evaluation can detect an elongated styloid process and calcification of the stylohyoid ligament. It has been reported that 2 – 28% of the general population show radiographic evidence of mineralization of a portion of the stylohyoid chain. The elongated styloid process may be symptomatic in many cases. Panoramic radiography is the best imaging modality to view the styloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
44
8
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 9 publications
15
44
8
2
Order By: Relevance
“…In the present study, it was found that type I elongation was more common than other types of elongation on both right and left sides and the data were statistically significant; these observations were similar to the findings reported by few other studies 23,27,29…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, it was found that type I elongation was more common than other types of elongation on both right and left sides and the data were statistically significant; these observations were similar to the findings reported by few other studies 23,27,29…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in accordance with Bozkir et al,19 Vadgaonkar et al,22 Roopashri et al23 and Shaik et al30 However, More and Aarani27 observed that the elongated styloid process was more common on the right side in their study population. Ilgüy et al6 and Custodio et al31 observed no difference in the length of the styloid process when the sides were compared.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that the calcified styloid was more prevalent in older subjects, which was in accordance with the previous findings that with ageing there was progression in styloid process elongation 13. Additionally, we noted that the male population had a predilection for styloid process elongation.…”
Section: Discussionsupporting
confidence: 92%
“…A study was performed on the population of the Davangere region of Southern India16 where 173 panoramic radiographs were reviewed and the incidence of mineralization of the styloid process was found to be 24.8%. Also, More and Asrani studied 500 digital panoramic radiographs of a population in the Gujarat region of Western India, and they found elongated styloid process in 19.4% of its subjects 13. Both these investigators favored the theory of ageing for styloid process elongation.…”
Section: Discussionmentioning
confidence: 99%